Sinister ironies: The Romanian translation of “L’Internationale” from an anthem of the oppressed to the last words of a tyrant - Cernat, Laura (chronotopos – A Journal of Translation History, 2025)
This article explores the cultural history around the publication of the Romanian translation of Pottier’s “L’Internationale” by C. Z. Buzdugan in 1900 in the socialist newspaper Lumea nouă, as well as the song’s subsequent contexts during the communist regime (1944–1989). Combining an etymologically and stylistically-informed comparative close-reading of Buzdugan’s translated text and Pottier’s original with an account of the coeval crisis of early Romanian socialism, I provide fresh insight into how Romania’s still ruralized, post-feudal social structures at the turn of the twentieth century influenced some omissions and insertions in this previously neglected early translation. Aside from contributing to translation history, this article also sheds light on the importance of remediation and performance in the process of shaping the meanings of a widely circulated text. Through an analysis of the chameleonic totalitarian appropriation of “L’Internationale” in the Romanian context and of its perusal in Ceaușescu’s cunning game of distancing himself from Soviet control and appeasing the West while continuing to oppress the population of his country, I reveal a dark facet of the song’s potential to animate masses. Finally, I zoom in on the dictator’s final intonation of the workers’ anthem before the execution squad as an iconic and ironic historical lesson about the power of repetition and brainwashing to hollow out the positive message of this text and reduce it to a memento of Ceaușescu’s own empty glorification. I use this example as a caveat against the treacherous powers of propaganda, which to this day threaten Romanian society.